Quality of life assessment and coping with stress in patients with shoulder injuries - Tarczyńska, Marta; Potembska, Emilia; Kowalska, Elżbieta; Pić, Jarosław; Kukuła, Barbara; Gawęda, Krzysztof (Current Problems of Psychiatry, 2013)
The objective of the study was to determine the dependence between the anxiety level and the self-image and stress coping strategies in patients with knee injuries and distinguishing personality traits that are the best predictors of anxiety in patients. Materials and Methods: The study included 32 patients (15 women and 17 men), hospitalised in Arthros Medical Center in Nałęczów, Poland, for knee injuries. The average age of the subjects was 31 years. The following methods were used in the study: The Adjective Check List by Gough and Heilbrun in the “what are you like” version, the author’s own questionnaire, R. Cattell’s IPAT Anxiety Scale - Self Analysis Form and the Stress Coping Questionnaire in the Polish adaptation of Januszewska. Results: Statistically significant dependencies were found between a high level of anxiety in patients with a negative self-image and non-adaptive, destructive stress coping strategies. The personality traits that best explain anxiety in the examined group of patients were identified using stepwise linear regression. Conclusions: A sense of significant changes in life and deterioration of its quality resulting from the knee injuries of patients coexists with an immature personality, impulsiveness and increased fear of being negatively assessed by others. The increased anxiety in patients is connected with negative self-image characteristics : adaptation difficulties, lack of autonomy, lack of coping skills with everyday life tasks, fear of establishing interpersonal relationships, the tendency to escape from reality into day-dreams, low frustration tolerance, lack of entrepreneurship, lack of perseverance in fulfilling tasks, lack of self-confidence and self-reliance. The increased anxiety in patients coexists with the use of passive coping strategies : escaping from problems, isolating oneself from people, reacting in difficult situations by prolonged concentration on own failures, giving up problem solving, self-blame, self- and other-directed aggression and alcohol abuse.